2014
DOI: 10.1016/j.jcrs.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal intraocular lenses: Relative indications and contraindications for implantation

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
169
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(201 citation statements)
references
References 49 publications
2
169
0
15
Order By: Relevance
“…32 Previous research has shown that dysphotopsia cannot be objectively explained by optical parameters per se, and it is accepted that neuroadaptation may lead to an improvement or resolution of these symptoms in the majority of patients. 5,13,32 We confirm the notion of objective versus subjective dissociation, because in this study there was also no correlation between patients' subjective visual symptoms and optical properties (total RMS, higher order RMS, average MTF, MTF for 10 cpd spatial frequency, and Strehl ratio) or contrast detection thresholds. Contrast detection thresholds were positively correlated with the total RMS, indicating that patients with more aberrations had a higher contrast detection threshold.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…32 Previous research has shown that dysphotopsia cannot be objectively explained by optical parameters per se, and it is accepted that neuroadaptation may lead to an improvement or resolution of these symptoms in the majority of patients. 5,13,32 We confirm the notion of objective versus subjective dissociation, because in this study there was also no correlation between patients' subjective visual symptoms and optical properties (total RMS, higher order RMS, average MTF, MTF for 10 cpd spatial frequency, and Strehl ratio) or contrast detection thresholds. Contrast detection thresholds were positively correlated with the total RMS, indicating that patients with more aberrations had a higher contrast detection threshold.…”
Section: Discussionsupporting
confidence: 75%
“…5 Neuroadaptation, defined as the neural changes induced by the new type of visual experience, is often highlighted as an important process in favorable multifocal IOL outcomes. However, no functional study addressing the human cerebral cortex in this setting has been done, to the best of our knowledge, 13,14 following PubMed database searches conducted by using distinct combinations (with AND and OR operators) of the terms functional, lenses, magnetic resonance, multifocal, neuroadaptation, dysphotopsia, and neurobehavioral.…”
mentioning
confidence: 99%
“…5 For this reason, multifocal IOLs are not recommended for eyes with significant irregular corneal astigmatism. 6 To prevent the formation of irregular astigmatic corneas following cataract surgery, an estimation of the change in corneal HOAs induced by the surgery and anticipation of a potentially risky cornea may be helpful. In our current study, we investigated changes in corneal HOAs in a cataract surgery patient series in accordance with the incision location of different axes (superior, temporal, and nasal).…”
mentioning
confidence: 99%
“…Understanding the patient's lifestyle requirements, visual goals, and personality traits are very important in determining candidacy for multifocal selection [6, 7]. Patients who are highly motivated for complete spectacle independence, able to accept a small compromise in distance vision, and convey a relaxed personality are often more successful with multifocal implantation [7]. Personality type is often correlated with successful neuroadaptation and the subsequent reduction of postoperative dysphotopsias (e.g., glare and halos).…”
Section: Discussionmentioning
confidence: 99%